Microscale purification in support of high-throughput medicinal chemistry. Issue 84 (5th October 2021) - Barhate, Chandan L.; Donnell, Andrew F.; Davies, Merrill; Li, Ling; Zhang, Yong; Yang, Fukang; Black, Regina; Zipp, Greg; Zhang, Yingru; Cavallaro, Cullen L.; Priestley, E. Scott; Weller, Harold N.
Abstract : High-throughput purification workflow in support of microscale (1–5 μmol or 0.5–2 mg) library synthesis. Abstract : In recent years, successful assay miniaturization has enabled the exploration of synthesis scale reduction in pharmaceutical discovery. Miniaturization of pharmaceutical synthesis and purification allows a reduction in material consumption and shortens timelines, which ultimately reduces the cost per experiment without compromising data quality. Isolating and purifying the compounds of interest is a key step in the library synthesis process. In this manuscript we describe a high-throughput purification workflow in support of microscale (1–5 μmol or 0.5–2 mg) library synthesis. The optimized microscale purification system can routinely purify 384-well reaction plates with an analysis time of 4 min per sample. Instrument optimization, critical parameters such as column loading, delay time calibration, ultrafast pre- and post-purification analysis and library purification examples are provided.